Pengaruh Motivasi Belajar Taruna Dan Kompetensi Dosen Terhadap Prestasi Belajar Taruna di Politeknik Penerbangan Surabaya - Sri Lestari (Jurnal Penelitian)
Motivation learn is the effort someone cadets to provide all energy condition to learn so that he will or wish process study. Lecturer play a part good enough important in the plan and also curriculum execution. Beside that lecturer is planner, curriculum developer and executor to its class, because lecturer also curriculum developer line which is terdepan hence lecturer also which always evaluate and completion to curriculum. From result of calculation with t test above it can be interpreted that cadet motivation / (X1), t value obtained is 17,264 and its significance value is 0.000, this value is smaller than = 0,05,Lecturer competence / (X2), t arithmetic value obtained is 14.255 and the significance value is 0,000, this value is smaller than  = 0,05meaning that cadet motivation (X1) and lecturer competence (X2) are partially significant to achievement learning cadets (Y) atAviation Polytechnic of Surabaya. The result of F Test calculation done with the help of SPSS program obtained F value counted 298,095. The significance value obtained is 0.000, the value of significance is smaller than the value of that is 0.05, meaning that cadet motivation (X1) and lecturer competence (X2) together significantly affect achievement learning cadets (Y) atAviation Polytechnic of Surabaya. The result of SPSS practice on standardized regression coefficient (β) or Standardized of Coefficients Beta, it is known that variable X2 that is cadet motivation has standardized coefficient of standard (β) or Standardized of Coefficients Beta is 2,542 compare with other independent variable variable X2 that is taruna motivation is independent variable that dominant influence dependent variable that isachievement learning cadets (Y) atAviation Polytechnic of Surabaya.